Urban gully erosion in sub‐Saharan Africa: A case study from Uganda. (29th December 2017) - Zolezzi, Guido; Bezzi, Marco; Spada, Daniele; Bozzarelli, Elisabetta
Abstract: The study examined gully erosion in Koboko, North‐western Uganda, initially a war refugee camp, which progressively turned into a permanent rural town. A repeatable, low‐cost methodology to quantify gully properties in data‐scarce, resource‐limited urban contexts is developed, which integrates collection of existing hydrological, land use data, topographic surveys, hydrological and hydraulic modelling, and interviews to local inhabitants and stakeholders. Four main gullies have developed in the last 10–15 years along the eastern, hillside of Koboko, with width‐to‐depth ratios not exceeding 3 and maximum scour depths of 9 m. Their length ranges between 270 and 460 m in the most densely populated area and is mostly unstable, especially for slopes exceeding 3%. Causes of the gullies include urban road development, changes in urban land cover to impervious surfaces, and inadequate planning of the urban drainage system. The gullies hamper the safety of people and buildings and increase health risks in an already vulnerable community. Slope–area and slope–road length thresholds suggest Koboko to be less susceptible to gullies compared to other reported urban contexts and support the anthropogenic origin of the observed gullies. The analysis allowed to design mitigation measures that still self‐sustain after 3 years of implementation. Results upscaled at country level can be used to predict which other urban centres in Uganda may be susceptible to gullying. Gullying in rapidly developing urban areas in sub‐Saharan Africa clearly show the co‐evolution of a social and a geomorphic system, which should be accounted for in urban planning to avoid adverse societal effects.